Enhancing Spiritual Care in Intensive Care Units: An Analysis of the Impact Nurses’ Knowledge, Motivation, and Competency - Ikbal, Revi Neini; Sari, Rebbi Permata (Journal of Health Sciences and Epidemiology, 2024)
Spiritual care, a vital component of holistic nursing, is often overlooked in intensive care units (ICUs) because of the limited knowledge, motivation, and competency of healthcare providers. This study investigated ICU nurses' knowledge, motivation, and skill in providing spiritual care. This cross-sectional study included 38 ICU nurses. A systematic questionnaire was used to evaluate nurses' knowledge, motivation, and competency in spiritual care. The relationships between these parameters were analyzed using univariate and bivariate analyses. The findings indicated that ICU nurses moderately understood spiritual care (M = 7.2, SD = 1.9) and exhibited strong motivation (M = 4.0, SD = 0.8). Skills in spiritual care were positively correlated with knowledge (r = 0.41, p < 0.05) and motivation (r = 0.52, p < 0.01). Previous spiritual care training markedly enhanced nurses' competencies (p < 0.05) and served as a significant predictor (β = 0.28, p < 0.05). This study underscores the critical role of knowledge, motivation, and competency in enhancing spiritual care among ICU nurses. Targeted interventions such as educational programs and institutional support are essential for improving spiritual care practices. Future research should focus on developing comprehensive training models to address the individual and systemic barriers to spiritual care integration in critical care environments.